Atrio-ventricular node radio-frequency ablation and modification: effects on quality of life in patients with non-valve atrial fibrillation - E. V. Minakov; S. A. Kovalev; N. V. Belov (Российский кардиологический журнал, 2006)
With a questionnaire «Arrhythmic Patient's Life» (APL), quality of life (QoL) dynamics was investigated in 54 patients with non-valve atrial fibrillation (AF), after radio-frequency ablation (modification) of atrio-ventricual node and pacemaker implantation. In patients with drug treatment-resistant arrhythmia, QoL improved after the surgery. Positive dynamics was observed in QoL aspects reflecting AF clinical severity, psycho-emotional status, and night sleep quality. According to APL questionnaire, QoL in AF patients was mostly affected by arrhythmia symptoms, deteriorated psycho-emotional status and night sleep, as well as the need for permanent and possibly costly treatment.